Analysis on acceptance level of Malaysian’s consumers towards purchasing imported rice: case study at Jasin, Melaka / Nik Luqman Hakim Zulkifle - Zulkifle, Nik Luqman Hakim (Faculty of Plantation and Agrotechnology, 2019)
Rice (Oryza sativa) was the most essential food crop which been cultivated worldwide. It was the second important food crop in the world after wheat and Asia was the largest producer and consumer of rice. In Malaysia, rice was a staple food for Malaysians despite the introduction of other food item. It’s production in Malaysia was low as compared with other countries that rice growing in the world. The objective of the study was to determine the factors that influence the acceptance level toward imported rice in Malaysia. Survey method was used for data collection. The questionnaires have been distributed to 200 respondents which 100 males and 100 females. Statistical Package for Science Computer Software (SPSS) were used to analysis result and interpret based on descriptive analysis and factor analysis. Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO) was 0.766 indicated that the value was acceptable which means factor analysis was appropriate for the data. Factor analysis result shows that price was the dominant attribute which represented by three factors that eigenvalues more than 1, factor 1 (quality), factor 2 (availability), and factor 3 (price). It was about 61.42% of the total variance explained by the factors. Therefore, it can be concluded the most dominant factor that influence acceptance level of Malaysian’s consumers toward purchasing imported rice was quality factor. As recommendation, producers need to improve the quality of rice based on government quality standards. One of the characteristics of a good quality rice is its long life. As we know that most imported rice have higher quality compared to local rice for example, Jasmine (imported rice) and ST15 varieties (local rice). If our rice meets the quality standards set by the government, it is not impossible for our rice to be a challenger of other rice imported from other countries.